catena-Poly[[trimethyltin(IV)]-μ-quinaldato] - Hongyun Wang (Acta Crystallographica Section E, 2008)
The title compound, [Sn(CH3)3(C10H6NO2)]n, forms an extended one-dimensional chain structure. There are two independent SnIV ions, both of which are in slightly distorted trigonal-bipyramidal coordination environments with two symmetry-related O atoms in the axial sites. In each case, the SnIV ion and one of the three equatorial C atoms lie on a crystallographic twofold axis.